Inventory of a Neurological Intensive Care Unit: Who Is Treated and How Long? - Roland Backhaus; Franz Aigner; Felix Schlachetzki; Dagmar Steffling; Wolfgang Jakob; Andreas Steinbrecher; Bernhard Kaiser; Peter Hau; Sandra Boy; Kornelius Fuchs; Ulrich Bogdahn; Markus Ritzka (Neurology Research International)
Purpose. To characterize indications, treatment, and length of stay in a stand-alone neurological intensive care unit with focus on comparison between ventilated and nonventilated patient. Methods. We performed a single-center retrospective cohort study of all treated patients in our neurological intensive care unit between October 2006 and December 2008. Results. Overall, 512 patients were treated in the surveyed period, of which 493 could be included in the analysis. Of these, 40.8% had invasive mechanical ventilation and 59.2% had not. Indications in both groups were predominantly cerebrovascular diseases. Length of stay was 16.5 days in mean for ventilated and 3.6 days for nonventilated patient. Conclusion. Most patients, ventilated or not, suffer from vascular diseases with further impairment of other organ systems or systemic complications. Data reflects close relationship and overlap of treatment on nICU with a standardized stroke unit treatment and suggests, regarding increasing therapeutic options, the high impact of acute high-level treatment to reduce consequential complications.